Directed evolution of Chlorella sp. HS2 towards enhanced lipid accumulation by ethyl methanesulfonate mutagenesis in conjunction with fluorescence-activated cell sorting based screening. (15th May 2022) - Nayak, Manoranjan; Suh, William I.; Oh, Young Taek; Ryu, Ae Jin; Jeong, Ki Jun; Kim, Minsik; Mohapatra, Ranjan Kumar; Lee, Bongsoo; Chang, Yong Keun
Graphical abstract: Schematic illustration of the present study. A directed evolution approach by EMS mutagenesis in conjunction with FACS-based selection was used to enhance the lipid productivity of Chlorella sp. HS2. Highlights: EMS mutagenesis with FACS was used for strain improvement of Chlorella sp . HS2. SMS showed high lipid content of 35.6% and lipid productivity of 248.7 mg L -1 d -1 . Cells that underwent mutagenesis had higher content of SFA (43.1%) and MUFA (33.6%). Biodiesel fuel properties of SMS (TE+F ) were compliant with US and EU standards. Abstract: The present study aimed to improve the lipid content and lipid productivity of Chlorella sp. HS2 by exposing them to ethyl methanesulfonate (EMS) to generate a mutant and followed with fluorescent assorted cell sorting (FACS) for the selection of mutant cells having desirable phenotypes. The microalgae were subjected under 100 μ mol mL −1 concentration of EMS for 30 min, followed by intracellular lipid staining with boron-dipyrromethene (BODIPY) fluorophore for FACS based selection. The biomass growth, lipid content, lipid productivity, and fatty acid composition of the selected mutagenized strain (SMS, TE+F ) of Chlorella sp. HS2 were compared against those of FACS selected strain without mutagenesis (FSS, TF ) and parent wild strain (PWS, TC ), under two different carbon supplementation schemes (only CO2 supply and optimized carbon supply). The highest lipid content and productivity of 35.6% and 248.7 mg L -1 d -1, respectively were observed in the SMS grown under optimized carbon supplementation (1% CO2 (v/v) and 0.5 g L -1 NaHCO3 ), which was a substantial improvement over those of FSS (26.6% and 193.4 mg L -1 d -1 ) and PWS (24.7% and 153.6 mg L -1 d -1 ). The fatty acid methyl ester (FAME) profile of the lipids derived from SMS showed a marked increase in the proportion of saturated fatty acids (SFA) and mono-unsaturated fatty acids (MUFA) (76.7%) over those of FSS (70.2%) and PWS (69.6%). Lastly, fuel properties were found to be appropriate for biodiesel production, as they corroborate with international fuel standards. These results indicate that directed evolution using EMS mutagenesis with FACS is a powerful tool to achieve microalgal strain improvement for biofuel production.